2008
DOI: 10.1074/jbc.m802803200
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding Protein CUGBP1 Regulates Stability of Tumor Necrosis Factor mRNA in Muscle Cells

Abstract: Type I myotonic dystrophy (DM1) is caused by a triplet repeat expansion in the 3-untranslated region (UTR) of the dystrophia myotonia protein kinase (DMPK) gene. Pathogenesis is closely linked with production of a toxic RNA from the mutant allele, which interferes with function of several RNA-binding proteins, including CUGBP1. Here we show that expression of a mutant DMPK 3-UTR containing 960 CUG repeats is sufficient to increase expression and stability of an mRNA encoding the potent proinflammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 36 publications
3
88
0
Order By: Relevance
“…In a myotonic dystrophy model, CUGBP1 was hyperphosphorylated by PKC␣ and ␤II, causing increased protein half-life and altered splicing patterns (19,30). Expression of a (CUG) 960 -expanded myotonic dystrophy protein kinase gene caused CUGBP1 phosphorylation and inhibition of CUGBP1-mediated decay of the TNF-␣ transcript (21). It is thought that CUGBP1 binds to a CG-rich motif in the (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a myotonic dystrophy model, CUGBP1 was hyperphosphorylated by PKC␣ and ␤II, causing increased protein half-life and altered splicing patterns (19,30). Expression of a (CUG) 960 -expanded myotonic dystrophy protein kinase gene caused CUGBP1 phosphorylation and inhibition of CUGBP1-mediated decay of the TNF-␣ transcript (21). It is thought that CUGBP1 binds to a CG-rich motif in the (24).…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of myotonic dystrophy, it has been shown that CUGBP1 is phosphorylated by protein kinase C (PKC), resulting in altered cellular distribution and stability of the CUGBP1 protein, correlating with altered splicing patterns (19,20). The CUGBP1 target transcript TNF-␣ was stabilized upon chemical activation of the PKC pathway (21). In addition, the RNA binding specificity of CUGBP1 has been shown to be altered via phosphorylation by cyclin D3-Cdk4/6 (22).…”
mentioning
confidence: 99%
“…Moreover, activation of the protein kinase C (PKC) pathway also stabilized the TNF transcript. These results suggest that the elevated serum TNF seen in DM1 patients may be derived from muscle where it is induced by expression of toxic DMPK RNA (Zhang et al, 2008). In a more recent study, Koshelev et al…”
Section: Cug Binding Protein 1 (Cugbp1)mentioning
confidence: 86%
“…Experiments performed in C2C12 mouse cell line showed that expression of a mutant DMPK 3'-UTR containing 960 CUG repeats is sufficient to increase expression and stability of an mRNA encoding the potent proinflammatory cytokine, tumor necrosis factor (TNF), which was found elevated in DM1 patients serum (Mammarella et al, 2002;Zhang et al, 2008). Moreover, activation of the protein kinase C (PKC) pathway also stabilized the TNF transcript.…”
Section: Cug Binding Protein 1 (Cugbp1)mentioning
confidence: 99%
“…In the DM1 disease model, there is aberrant activation of the protein kinase C pathway as a result of the CTG expansion, and this results in CELF1 phosphorylation. Mouse myoblasts (C2C12 cells) made to express CTG expanded RNA were shown to experience stabilization of tumor necrosis factor alpha (TNF-alpha) mRNA [143]. This result suggested that the overexpression of TNF-alpha observed in DM1 could be coming from muscle, and this TNFalpha overexpression may contribute to the muscle wasting and insulin resistance that are characteristic of this disease [143].…”
Section: Mrna Decaymentioning
confidence: 99%